Profile of people with suicidal behavior and pre-existing mental health illnesses before the COVID-19 pandemic and during the first 6 months of pandemic: Comparative study by time periods and by gender. - Mahulea, Liliana; Domínguez-García, Marta; Millán-Taratil, María; Ruiz-Herrero, María; Serrano-Ripoll, Mª Jesús (Acciones e Investigaciones Sociales, 2023)
Introduction:The aim of this study is to analyze and compare the profile of people with suicidal behavior 6 months before the pandemic and during the first 6 months after its onset, in a cohort of patients with previous high prevalence mental health illnesses, using Primary Health Care (PHC) records.Methodology: A retrospective, longitudinal and comparative study. We collected data on sociodemographic, pre-existing mental health illnesses or new diagnoses, COVID-19 infection, use of health resources during the study period where the suicide attempt or suicide occurred. A bivariate analysis was performed comparing by gender and by the time period during which the suicidal behavior occurred, as well as a multivariate logistic regression analysis.Results: In Aragón (Spain), 173 persons were reported with suicidal behavior during the 6 months prior to the onset of the pandemic, and 153 persons during the 6 months after, with no changes in the sociodemographic profile.The participant profile was that of a woman, with a preexisting episode of depression and/or anxiety. Lack of contact with the health system, especially with the health center social worker and the continuing care services increased the risk of suicide during the pandemic.Conclusions: Contact with the health care system in future pandemics is important for the prevention of suicidal behavior.
Keywords: suicide; pandemic; COVID-19; pre-existing mental illness; health and social services